Non-nutritive sweeteners and their impacts on the gut microbiome and host physiology - Richardson, Irene L.; Frese, Steven A. (Frontiers in Nutrition, 2022)
Non-nutritive sweeteners (NNS) are broadly incorporated into foods, especially those representing a growing share of the beverage market. NNS are viewed as a noncaloric and desirable alternative to sugar-based sweeteners and are thought to contribute to reducing overall caloric intake. While these compounds have been studied extensively and have long been considered inert, new research has presented a different view and raises new questions about the effects of NNS on human physiology. Namely, the influence on glucose responses, the gastrointestinal epithelium, and the gut microbiome. As the gut microbiome is now recognized as a major mediator of human health and perturbations to this community are generally associated with negative health trajectories or overt disease, interactions between NNS and the gut microbiome are of increasing interest to clinicians and researchers. Several NNS compounds are now hypothesized to affect human physiology by modulating the gut microbiome, though the mechanism for this action remains unclear. The purpose of this review is to discuss the history and current knowledge of NNS, their reported utility and effects on host physiology and the gut microbiome, and describes a model for investigating the underlying mechanism behind reported effects of NNS on the gut microbiome.